Settlement of Litigation and Non-Litigation Disputes in Sharia Economic Cases: A Case Study of The Musyarakah Contract - Nurhikmah, Aulia; Madani, Farid; Sunaryo Mukhlas, Oyo (Zona Law And Public Administration Indonesia, 2025)
Disputes can be resolved through litigation (in court) or non-litigation (out of court). Dispute resolution through litigation involves examining disputes before a judge in court. Whether it's public or private disputes, litigation, or court, are the most common dispute resolution methods. As time goes by, people's needs for justice and welfare increase. As a result, dispute resolution through litigation has become less effective. This is considered too long and costs quite a lot. In situations like this, people who seek justice begin to look for other options, namely dispute resolution outside the judicial process, which is called dispute resolution that does not involve litigation, i.e. non-litigation is carried out and the role of mediators. In the aspect of settlement using non-litigation methods for a quick and cheap settlement through the role of mediators in non-litigation dispute resolution through the negotiation stages, mediation, conciliation, and arbitration are some of the methods of resolving disputes outside of court. The discussion of the Musyarakah Contract is a form of financing that is commonly used in Islamic financial institutions. This research uses a normative approach to research to reveal the truth systematically, methodologically, and consistently. This approach has been collected and processed, analyzed and used for constructive purposes during the research process, how effective the role of mediators is in non-litigation dispute resolution